PROSPECTIVE WAYS FOR POST-WAR DEVELOPMENT OF UKRAINIAN ENTERPRISES - NAMIASENKO, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines a range of potential prospective ways for the development of Ukrainian enterprises during the period of post-war recovery and development of Ukraine. The examined paths are categorised based on the size of the enterprise, as well as their financial and resource capacity and competitiveness.The article aims to formulate an unexhaustive and concrete list of potential developmental avenues for Ukrainian enterprises, depending on their size, during the post-war recovery and development period.A limitation of the study is the assumption of effective post-war governance by the Ukrainian government.The study of the historical experiences of post-war recovery and development of European and Asian countries formed a hypothesis on the necessity of creating post-war development strategies based on large enterprises and the diversification of their activities and simultaneously supporting small and medium-sized enterprises. Such actions aim at both the development and prevention of market monopolisation.It has been determined that powerful agroholdings are the most promising, with the potential to diversify their activities into biogas production, logistics and warehousing, product IT, precision engineering (including defence industry products) and tourism and recreational medicine. The chosen developmental paths are based on Ukraine’s natural advantages, including numerous recreational areas and historical sites and significant experience in engineering, IT outsourcing and product IT. A significant benefit is Ukraine’s location at the intersection of many crucial land and sea logistics chains and nodes.Small enterprises’ activities should be oriented toward geographical location and the presence of a large anchor enterprise. Government support must be directed toward transforming business practices to a more professional level and identifying priority sectors.The study results are not exhaustive due to the high variability of war termination scenarios and necessitate further elaboration of the identified issues to maximise economic security and potential.
Keywords: post-war development of enterprises; diversification of activities; development of agricultural holdings; the experience of Asia and South Korea; priority areas of post-war development